(untitled) (Patrimônio e Memória, 2019)
The present text aims to generate reflections on the role played by the visual arts, with special emphasis on the painting of Fernando Botero, which shows in one of his collections donated by the painter to Colombia, great interest in retaking violent events in the country which currently they continue to be remembered sporadically. To sustain this issue, the thinking of authors such as Michael Pollak, Gaborit Pascaline, Santiago Londoño, among others, is taken up in terms of an interdisciplinary dialogue between art and memories of tragic events in post-conflict times. Finally, a little is inquired into the role of heritage, assigned by Colombian governmental entities to the canvases of the painter, a role in which his memorial intention is ignored but his tendency to show folklore and customs. This topic opens the doors for further investigative analyzes related to the “underground memories” of the conflict of the late twentieth century and early 2000s in Colombia.